POST STROKE COGNITIVE IMPAIRMENT IN RURAL HOSPITAL: A COMPARATIVE ANALYSIS OF MOCA-INA AND MMSE - Rumondang Silalahi, Valeria (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Introductions: Post-stroke Cognitive Impairment (PSCI) is a long-term complication that may occur three months after a stroke. This cognitive impairment can range from mild to severe and may progress to dementia. The Mini-Mental State Examination (MMSE) and the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) are commonly used screening tools for early detection of cognitive dysfunction due to their simplicity. However, data on their sensitivity in the Indonesian population is still limited. Objectives: This study aims to compare the proportion of cognitive impairment identified by MMSE and MoCA-Ina in post stroke patients at the Neurology Polyclinic of Hadrianus Sinaga Hospital, Samosir Island. Methods: This analytical, cross-sectional study was conducted on 49 samples that fulfilled the inclusion and exclusion criteria. Consecutive sampling was used, and data were analyzed using SPSS version 30.0 Results: Based on sociodemographic characteristics, most participants were male (67.3%), over 60 years old, and had a high school education. PSCI was identified in 34.7% of patients using the MMSE, while the MoCA-Ina detected impairment in 81.6%. Among patients with MoCA-Ina scores below 26, 57.5% had MMSE scores of 24 or higher. For severe cognitive impairment, 11 patients had MoCA-Ina scores below 18, seven of them had an MMSE score of 17 or higher. These differences were statistically significant (McNemar’s test, p <.001 and p .016). Conclusion: MoCA-Ina is more effective than MMSE in detecting early cognitive dysfunction in post stroke patients and may be recommended as a routine screening tool. Keywords: Post-stroke Cognitive Impairment, MMSE, MoCA-Ina.